Steam-Based Loose Part Learning Media Can Build Independent Learning Early Children - Purwanti Purwanti; Zulkarnaen Zulkarnaen (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2023)
This study aimed to analyze how learning media with loose-based media functions as an effort to build early childhood learning independence. This research used descriptive qualitative method. Research data collection techniques used observation and interviews. The research was conducted at TK Aisyiyah Bustanul Athfal 1 Wonosegoro with a total of 16 research subjects consisting of 11 female students and 5 male students. The research stages started from lesson planning to evaluation and follow-up learning. The research showed that learning with loose parts could provide freedom to play and build learning independence for early childhood. This can be seen in the increase in children's creativity, encouraging children to be active in learning, increasing children's independence, training children's ability to work together, and building of self-confidence in children. The teacher's strategy in taking advantage of the teacher's leeway is to organize a comfortable playing environment for children. Part of learning is that children can determine the play activities and materials they want.